PENDEKATAN DEEP LEARNING BERBASIS TPACK DI TINJAU DARI PERSPEKTIF PSIKOLOGI PENDIDIKAN DI SMP NEGERI 1 SITURAJA - Siregar, Julinda; Wartini, Nani; Nia Kurniasih, Enok; Wintarsih, Ade; Juliana Soleh, Mega; Marsam, Thoif; Afriani, Risma; Nurul Hidayah, Rizky; Oktovia; Setiawati, Aini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of a deep learning approach based on Technological Pedagogical Content Knowledge (TPACK) from the perspective of educational psychology at SMP Negeri 1 Situraja. The study employed a qualitative descriptive method involving teachers and eighth-grade students as research subjects. Data were collected through observation, interviews, and documentation techniques. The findings revealed that the implementation of TPACK-based deep learning was able to improve students’ learning motivation, critical thinking skills, communication abilities, and active participation during the learning process. Teachers utilized various digital media such as Google Classroom, Canva, PowerPoint interactive presentations, and learning videos to support meaningful learning experiences. From the perspective of educational psychology, this approach positively influenced students’ cognitive, affective, and social development through collaborative and student-centered learning activities. However, several challenges were identified, including limited technological facilities, unstable internet access, and varying digital competencies among teachers and students. Therefore, improving teachers’ digital competencies and providing adequate technological infrastructure are necessary to optimize the implementation of TPACK-based deep learning in schools.